(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
Two surface sections of Mukdadiya Formation, namely; Al-Band and Bajaliah in eastern Iraq are selected to conduct the geochemistry of sandstone. Fifteen sandstone samples were analyzed using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) and fused XRF techinques to determine the content of major oxides ( SiO2, Fe2O3, TiO2, Al2O3, CaO, K2O, Na2O, SO3, L.O.I); trace elements(Cr, Ni, Co, V, Sc, Zr, Hf, Ta, Nb, Th, U, Y, Rb, Sr) and rare earth elements, REE( La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu). SiO2 versus (Al2O3+K2O+Na2O) diagrams indicated that Mukdadiya sandstone was deposited under arid to semi-arid paleo-climate condition. The elemental ratios based on Cr, Ni, Co, V, and Sc indicate that andesite are as source rocks of sandstone. Zr, Hf, Th, U and Sr, tend to increase in sand samples because of their highly resistance to chemical weathering. Also, Nb/Y vs. Zr/TiO2 diagram shows that the andesite is a source rock of Mukdadiya sandstone. Furthermore, the elemental ratios ΣLREE/ΣHREE, LaN/LuN and Eu/Eu* show an enrichment of LREE with the grain size decrease and with increase of clay fraction in the sand samples. La-Th-Sc triangular discrimination diagram reveals that Mukdadiya sandstones are plotted in the continental arc field. The REE patterns indicated the contribution of both intermediate (andesite) and basic (basalt) igneous rocks to be the expected source of Mukdadiya sandstone.